WHITE PRIVILEGE IN AUSTRALIA: MIGRANT UNDERSTANDING ANALYSIS AND THE ROLE OF INTERNASIONAL ORGANIZATION FOR MIGRATION IN ENCOURAGING RACIAL AWARENESS - M. Fathan Karib; M. Farid Pratama; Amirah Zharifah; M. Nurbasyarullah QRW (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2026)
This research analyses migrants' understanding of the concept of white privilege in Australia and evaluates the role of the International Organization for Migration (IOM) in raising racial awareness among migrant communities. Using a qualitative approach with a descriptive analysis method that uses literature study techniques through various sources such as books, journals, and digital sources. Using the concept of international Organizations, this study found that many migrants have a limited understanding of white privilege, which is often influenced by their cultural background and personal experiences. IOM plays a vital role in facilitating intercultural communication, providing education on racial dynamics, and promoting inclusivity through various integration programmes. This research recognises the need for more participatory and contextualised strategies to build greater racial awareness among migrants, and assesses the importance of cooperation between international agencies, governments and local communities in addressing the issue of racial discrimination in Australia. Through this research, it was found that the awareness of both local and migrant communities regarding racial issues is still very low due to the hidden and systematic issue of white privilege and the role of IOM as an instrument, arena and actor.